Pengaruh Gaya Kepemimpinan Hybrid Dan Lingkungan Kerja Terhadap Peningkatan Kinerja Karyawan (Studi Kasus Pada PT. Belitang Panen Raya 1 Oku Timur, Sumatera Selatan) - Susanti, Rini; Khalikussabir, Khalikussabir; Utama, Satria Putra (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This study analyzes the effect of Hybrid Leadership Style and Work Environment on Employee Performance at PT. Belitang Panen Raya 1. This study’s sample consisted of 100 respondents selected using purposive sampling. Data were collected through questionnaires and analyzed using multiple linear regression analysis to determine the extent to which the independent variables (hybrid leadership style and work environment) influence the dependent variable (employee performance). The results indicate that, mathematically, the Hybrid Leadership Style has a positive relationship but does not have a significant impact. In contrast, the Work Environment has a positive and significant effect on Employee Performance. Keywords: Hybrid Leadership Style, Work Environment, Employee Performance